Forma prawna zaleceń konserwatorskich - Dubiński, Łukasz (Studia Prawa Publicznego, 2023)
The discussion in this study deals with the legal form of conservation recommendations. This concerns documents issued by conservation services, which define the way of using the monument, its protection and performance of conservation works, as well as the scope of permissible changes that may be introduced to this monument. In simple terms, the conservation recommendation is a “monument operating manual”, which is issued individually for each building by the competent voivodeship historic preservation officer. The legislator did not specify the legal form of this document. Therefore, in numerous studies one can find a number of standpoints on this issue. Undoubtedly, such discrepancies are not conducive to implementing the principles behind the adoption of the regulation on conservation recommendations, i.e. effective protection of monuments. This article analyses the concepts that dominate the doctrine. This is primarily a matter of accepting that conservation recommendations are issued in the form of an administrative promise or an act of knowledge. The concept according to which there is no single legal form appropriate for all conservation recommendations is also examined. At the same time, an attempt is made to discuss the most frequently negated assumption, according to which conservation recommendations could be issued in the form of administrative decisions. The discussion is conducted on the basis of the legal text and academics’ analysis of the doctrine. An important element of the discussion is that it compares the characteristics of the administrative decision with the properties of the legal forms in which, according to the doctrine, conservation recommendations are issued. The conclusion that can be drawn from the analysis presented here is that it would be appropriate to classify the conservation recommendations as administrative decisions.